2013
DOI: 10.3892/mmr.2013.1283
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative activity of daidzein and genistein may be related to ERα/c-erbB-2 expression in human breast cancer cells

Abstract: Abstract. In this study, we investigated the antiproliferative activity of the isoflavones daidzein and genistein in three breast cancer cell lines with different patterns of estrogen receptor (ER) and c-erbB-2 protein expression (ERα-positive MCF-7 cells, c-erbB-2-positive SK-BR-3 cells and ERα/c-erbB-2-positive ZR-75-1). After treatment at various concentrations (1-200 µM for 72 h), the effect of daidzein and genistein on the proliferation of different cell types varied; these effects were found to be associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 26 publications
3
49
0
Order By: Relevance
“…1), which is expected to interact effectively with estrogen receptors therefore inhibiting estrogen synthesis 17,57,58 and leading to a growth inhibition of MCF-7 cancer cells. In turn, for the MDA-MB-231 cells lacking estrogen receptors, daidzein is suggested to affect cell proliferation and viability by interference with different metabolic pathways, namely through cell cycle arrest (changes in regulatory proteins) and induction of apoptosis (via activation of caspases).…”
Section: Mcf-7mentioning
confidence: 99%
“…1), which is expected to interact effectively with estrogen receptors therefore inhibiting estrogen synthesis 17,57,58 and leading to a growth inhibition of MCF-7 cancer cells. In turn, for the MDA-MB-231 cells lacking estrogen receptors, daidzein is suggested to affect cell proliferation and viability by interference with different metabolic pathways, namely through cell cycle arrest (changes in regulatory proteins) and induction of apoptosis (via activation of caspases).…”
Section: Mcf-7mentioning
confidence: 99%
“…The abovementioned study reported that women consuming isoflavonecontaining supplements had a reduced risk for breast cancer in Ontario, Canada [11]. Clinical studies are also supported by in vitro studies indicating that isoflavones, mainly genistein, exhibited antiestrogenic activities at higher concentrations (>20 µM) and thus inhibited the proliferation of breast cancer cells [12,13].…”
Section: Introductionmentioning
confidence: 80%
“…Daidzein reported to possess strong anti-proliferative, anti-inflammatory and anti-fibrinolytic activity (Choi et al, 2013;Danyelle et al, 2008). Thus, in this study results of different evaluation such as visual score, histological analysis and hydroxyproline content suggested the potential effect of daidzein against the intra articular adhesion in post operative case.…”
Section: Discussionmentioning
confidence: 99%